PENGARUH PEMBERIAN VITAMIN C TERHADAP SUSUT BOBOT DALAM PENGANGKUTAN SAPI DARI LAMPUNG KE BENGKULU - Aufa, Ibnu Abi; Rudiono, Didik; Adhianto, Kusuma (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
Body weight of cattle would be lose about 10-30% during transportation because of stress. The condition affected on cattle business. Vitamin C could reduce stress, so itâs assumed that vitamin C treatment could reduce weight lost during transportation. An operation research was done on May up to August, 2014 to evaluate the effect ofÂ  vitamin C treatment on weight lost of during transportation from Lampung Province to Bengkulu Province.. Two group of cattle were observed in this research, 60 heads of the first group got 500 mg vitamin C treatment and 60 heads as control. Varibale observed were body weight of cattle before and after transportation. Quarrel between body weight before and after transportation were weight lost. Weight lost of cattle of the treatment group and the control group were analysed by t tests. This research indicated that weight lost ofÂ  treatment group were not different with control group (P>0,05).It could be concluded that 500 mg vitamin C had not reduced yet stress condition of cattle during transportation. It was suggested to increase dose of vitamin C in the next research. Keywords : Vitamin C, transportation, and weight lost.